Preserving Local Traditions of Sumbawa; Phenomenological Study of Artists Entering Batu Nisung State Elementary School - Andriani, Wiwin; Sumiadi, Raden (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to describe the program for the preservation of Sumbawa local wisdom values at SD Negeri Batu Nisung. This research is designed with a phenomenological approach. In obtaining data, the researcher plays the role of the main instrument with other supporting tools such as observation guidelines and interview guidelines. The data obtained through observation activities, interview activities and documentation were then analyzed using the Miles and Huberman model. The validity of the data was confirmed through triangulation, peer discussions and fukus group discussions. Based on the results of data analysis, it shows that at SDN Batu Nisung there is one program that aims to preserve local traditional values, namely Batu Nisung or SEMANIS. The program can introduce and train students as local traditional actors, because they are taught directly by local artists in playing traditional Sumbawa musical instruments. The Semanis program is part of a strategic step that connects the world of education with cultural arts so that it can create a collaborative space for students to develop their creativity, empathy, and insight into local cultural values.